Teknik Kesah Sebagai Upaya Pengendalian Diri Dalam Persaudaraan Setia Hati Terate (PSHT) Ranting Pulau Panggung Kabupaten Tanggamus: Perspektif Tasawuf Akhlaki - Ukayna Pramesti Bawono Putri; Agung M. Iqbal; Nesia Mu’asyara (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the practice of kesah as an effort to control oneself in the Persaudaraan Setia Hati Terate (PSHT) Branch of Pulau Panggung Regency, Tanggamus and to examine it from the perspective of moral Sufism. Kesah in the context of PSHT is not only a form of physical or spiritual exercise, but also a manifestation of the process of tazkiyatun nafs (purification of the soul) to achieve noble morals. This study uses a qualitative approach with a descriptive qualitative type. Data collection techniques are carried out through observation, in-depth interviews, and documentation. and documentation. The results of the study indicate that the practice of kesah is a means to train patience, reduce anger, and strengthen self-control of PSHT members in facing life's challenges. From the perspective of moral Sufism, kesah reflects the process of internalizing values ​​such as patience, humility, and sincerity which contribute to the formation of a balanced spiritual personality. Thus, kesah is not only part of self-defense training, but also a method of developing the soul towards a person with noble morals in accordance with the teachings of moral Sufism.